Democracies in the plural: A typology of democratic cultures. (May 2015) - Ferrara, Alessandro
This article aims at exploring one specific facet of pluralism: How can we conceive of a variety of democratic cultures that are not just local adaptations of one basic western-centric understanding of the democratic ethos? Drawing on Islamic, Jewish, Hindu, Buddhist and Confucian sources, a convergence among diverse democratic cultures is cursorily highlighted on such elements as the priority of the common good, the acceptance of pluralism, the desirability of collegial deliberation, the equality of citizens, and the value of individuality. Then two important points of dissonance are analysed in greater detail – (1) the idea of the priority of rights over duties and (2) the role of political conflict within a democratic polity – and shown not to be correlative with a divide between western and non-western contexts. Finally a typology of 4 kinds of democratic cultures is outlined.